IMPACTS OF MARINE SAND MINING ACTIVITIES TO THE COMMUNITY OF LONTAR VILLAGE, SERANG - BANTEN - Semeidi Husrin; Joko Prihantono; Hadi Softyan (BULLETIN OF THE MARINE GEOLOGY, 2014)
Marine sand mining activities in Lontar Village have been started legally since 2003 and temporarily halted in 2013. The locals blamed the activities for severe environmental destruction in almost every corner of the village such as low productivity ofaquaculture, coastal erosion, and habitat loss. This paper has an objective to provide preliminary data and analyses for environmental impact assessment of marine sand mining in Serang (Lontar Village). Field investigations were carried out in June 2014 to collect primary data such as bathymetrical data and water quality parameters in the region to understand the environmental conditions after 10 years of marine sand mining activities as well as the characteristicsof local oceanography. Extensive interview with the locals were also conducted to collect information about the socio-economic conditions of the village. Field findings showed that LontarVillage have experienced critical environmental problems such as coastal erosion, high turbidiy and loss of marine lives. Moreover, we also found that the abandoned aquaculture fields have also been converted as sand mining quarries. Recommendations to reduce further environmental damage in Lontar Village are proposed considering both socio-economy and physical aspects. Keywords:sand mining, Lontar village, environmental damage, erosion Aktifitas penambangan pasir laut di Kampung Lontar telah dimulai secara legal sejak 2003 dan telah berhenti untuk sementara tahun 2013. Keberatan penduduk setempat terhadap aktifitas penambangan tersebut adalah disebabkan oleh adanya gangguan lingkungan di hampir setiap sudut perkampungan seperti rendahnya produktifitas budidaya perikanan, erosi pantai dan hilangnya. berbagai aneka ragam habitat. Tujuan penelitian ini adalah untuk mendapatkan data awal dan analisis terhadap pengaruh lingkungan akibat aktifitas penambangan pasir laut. Penyelidikan lapangan telah dilaksanakan pada bulan Juni 2014 yaitu untuk mengumpukan data sekunder seperti batimetri dan parameter kualitas air di kawasan tersebut. Penelitian ini adalah untuk mengeahui kondisi lingkungan setelah 10 tahun aktifitas penambangan pasir laut, begitu juga karakteristik oseanografi daerah tersebut. Wawancara intensif dengan penduduk lokal telah dilakukan juga untuk mengumpulkan informasi tentang kondisi sosial ekonomi perkampungan tersebut. Temuan lapangan menunjukkan bahwa perkampungan Lontar mengalami masalah lingkungan yang kritis seperti proses erosi pantai, kekeruhan yang tinggi, dan hilangnya kehidupan laut. Lebih lanjut lagi penelitian ini telah menemukan bahwa sekumpulan ladang budidaya perairan telah beralih menjadi tambang pasir. Saran untuk memperkecil kerusakan lingkungan lebih jauh di Perkampungan Lontar, diusulkan pertimbangan aspek sosial ekonomi dan aspek fisik. Kata kunci : tambang pasir, Perkampungan Lontar, kerusakan lingkungan, erosi.